(untitled) (Texas Journal of Engineering and Technology, 2022)
This article discusses the integrity and continuity of computer science in the system of continuing education. Before we talk about the problems and prospects of teaching computer science, we need to consider the main problem. That is, to develop students’ understanding of the role of computer science as a science and the goals and objectives of its other branches.